Alirocumab Administration Experience to Achieve Low Density Lipoprotein Cholesterol Target Levels in Secondary Prevention of Cardiovascular Disease - A. E. Nikitin; E. E. Averin; D. E. Rozhkov; A. V. Sozykin; G. A. Procenko (Рациональная фармакотерапия в кардиологии, 2020)
Aim. To study the effects of proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor, alirocumab, on lipid levels in patients who receive secondary prevention of cardiovascular diseases (CVD) and require enhanced lipid-lowering therapy.Material and methods. The study included 49 patients (aged of 61.53±1.14 years; 31 [63.3%] men) receiving alirocumab who did not reach the target low density lipoprotein cholesterol (LDL-C) concentrations despite the ongoing optimal lipid-lowering therapy. In all patients, the initial level of lipids was evaluated, as well as their parameters after subsequent alirocumab injections.Results. LDL-C serum level significantly decreased after the first injection compared to the initial level from 2.92±0.22 to 1.65±0.19 mmol/L (p<0.001; Δ45.31±3.61%) and down to 1.74±0.17 mmol/L for the entire study period (p<0.001; Δ41.52±2.69%). The change in LDL-C level between injections did not show statistically significant differences (p=0.141). A direct strong statistically significant correlation between the LDL-C level after the first injection and its average values for the entire observation period was found (r=0.958, p<0.001).Conclusion. The results of the study indicate that the PCSK9 inhibitor, alirocumab, in patients who need secondary prevention of CVD shows a significant additional decrease in the concentration of LDL-C after the first injection. At the same time, approximately half of the patients were able to achieve the recommended levels of LDL-C. The persistence of the achieved low LDL-C levels over time demonstrated that the average concentration of LDL-C during the observation corresponded to the values after the first injection. This finding shows that there is no need for constant monitoring of lipid metabolism parameters when prescribing such therapy.